"It's changing our lives, not for the better. It's important that we have a say". The role of young people in informing public health and policy decisions about gambling marketing - Hannah Pitt; Simone McCarthy; Melanie Randle; Grace Arnot; Mike Daube; Samantha Thomas (BMC, 2024)
Abstract Background Marketing has a significant impact on the normalisation of gambling for youth across the globe. This has included shaping positive attitudes towards gambling, as well as increasing the social and cultural acceptance of gambling - particularly aligned with valued activities such as sport. Because of this, public health experts argue that gambling marketing poses a significant risk to the health and wellbeing of youth. While young people are increasingly exposed to, and impacted by marketing for gambling products, they are rarely consulted about policy issues and options. This study aimed to explore young Australians' perceptions of current policy responses to gambling advertising, whether they thought young people should be involved in discussions and decisions about gambling marketing regulations, and their perceptions of the duty of governments to protect young people from gambling industry marketing strategies. Methods Qualitative focus groups (n = 22) were held with n = 64, 12-17 year olds in the Australian states of Victoria and New South Wales. Participants were asked to reflect on current gambling policies, particularly relating to marketing, what they thought should be done about gambling marketing, and if and how young people should be included in public health responses to gambling. An interpretivist 'Big Q' approach to reflexive thematic analysis was used. Results Young people highlighted the need for more effective regulations around the content and frequency of gambling marketing. They also wanted to see more realistic representations of the negative impacts of gambling to counter persistent positive commercial marketing messages. Most thought that young people should be given an opportunity to have a say about responses to gambling due to their unique experiences. Participants identified mechanisms to increase young people's engagement in decision making, such as direct lines of communication to different levels of government, involvement in research, and diversifying ways of engagement. Specific recommendations included more regulatory action such as bans on gambling advertising. Conclusions Creating formal structures that facilitate the inclusion of young people's perspectives in decisions made about gambling can result in more innovative and effective strategies to prevent the harms from gambling industry products, promotions, and practices.